Anti-angiogenic activities of glycoalkaloids isolated from Solanum lyratum in tumor-derived vascular endothelial cells. (February 2019) - Han, Lin; Wang, Jian-nong; Sun, Cai-xia; Cao, Xiao-qiang; Du, Xiao
Graphical abstract: Highlights: One known and three novel glycoalkaloids were isolated from Solanum lyratum Thunb. Tumor-derived vascular endothelial cells (Td-ECs) obtained from a co-culture system were used in this study. Four compounds isolated from S. lyratum Thunb. indicated anti-angiogenic activities. Abstract: We previously identified alkaloids as being the main antitumor constituents of Solanum lyratum Thunb. In this follow-up study to identify the specific active principles, three new glycoalkaloids (1 –3 ) were isolated from S. lyratum with one known glycoalkaloid (4 ). The structures of the four compounds were determined by means of integrated spectroscopic techniques, as well as by comparison with those in literature. Furthermore, the effects of compounds1 –4 were investigated on repressed migration, invasion, and tube formation in vitro in tumor-derived vascular endothelial cells (Td-ECs) from a co-culture system established in the presence or absence of vascular endothelial growth factor (VEGF) at safe concentrations selected using a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, indicating anti-angiogenic activities.